Home and Neighborhood Context of Falls Among Black and White Older Americans. (October 2021) - Okoye, Safiyyah M.; Samuel, Laura J.; Fabius, Chanee; Mulcahy, John; Reider, Lisa M.; Szanton, Sarah L.; Wolff, Jennifer L.
Objectives: To examine social and physical environmental fall-risk factors in a nationally representative sample of community-living older adults overall and by racial group.Methods: We used data from the 2015 and 2016 rounds of the National Health and Aging Trends Study ( n = 5581) linked to census tract measures from the American Community Survey. Recurrent falls are defined as 2+ self-reported falls over 12 months.Results: Older adults with recurrent falls were more likely to have lower education, lower income, financial hardship, live in homes with disorder and disrepair and in neighborhoods without sidewalks, with high social deprivation, and in nonmetropolitan counties. Home disrepair, lack of sidewalks, and residence in a nonmetropolitan county were important fall-risk factors among White older adults only. Financial hardship was an important risk factor among Black older adults.Discussion: Environmental factors are associated with recurrent falls among older Americans and should be incorporated into fall-risk profiles and prevention efforts.